Representasi kasih sayang dan kesetiaan dalam filem Hachiko Monogatari / Tan Swee Ching - Tan, Swee Ching (2018)
The film, Hachiko Monogatari is a tragic true story about a dog named Hachiko (ハチ公). This dog was very loyal to its master, Professor Ueno, even after its master died. The film was aired in 1987 and was the highest rating box-office Japanese movie of that year. The American show "Hachiko: A Dog's Story" from 2009 was a remake of the Japanese version Hachiko Monogatari. This study aims to analyze the representation of love and loyalty in the film Hachiko Monogatari from a semiotic perspective. This study is based on the framework of Charles Sanders Peirce’s (10 September 1839 - 19 April 1914) Triadic Semiotic System. Clearly in Peirce's mind, there is an inseparable connection between sign and interpretation with the object he referred to. This study is a qualitative research using a descriptive approach. Semiotic analysis of verbal and non-verbal elements was created using Charles Sanders Peirce theory where descriptive methods were used to interpret data. Findings showed that the value of love can be represented by verbal and non-verbal elements. In terms of verbal elements, dialogue of character is seen. The verbal element was successfully analyzed based on Appraisal Theory (Teori Penilaian) (Martin & White, 2005; Martin & Rose, 2003) regarding attitude (sikap). In terms of non-verbal elements, body contact (touch of the body), proximity, facial expression, gesture, posture, and eye contact are seen. The non-verbal element was analyzed based on the meaning of Michael Argyles’ (1972) non-verbal communication language. The main character in the film, Professor Ueno was examined through verbal and non-verbal elements who showed attitude and feelings of love towards Hachiko. Loyalty can be represented through non-verbal elements. Non-verbal elements of loyalty were also analyzed based on the interpretation of Michael Argyles’ (1972) nonverbal language. The representation of loyalty in the film was seen through Hachiko’s behaviour to its master. Dogs cannot communicate verbally like humans, hence Hachiko’s loyalty to its master can only be scrutinized through non-verbal elements. The analysis of the film for significant signs in the film Hachiko Monogatari have delivered the keystone message on the values of love and loyalty contained in the film. The values of love and loyalty presented in the film Hachiko Monogatari have made this movie a success. Therefore, it is recommended that this film be used as learning material for students in school. The researcher is of the opinion that moral values such as love and loyalty should be learnt, emulated and nurtured in everyone's mind from primary school age.